2021
DOI: 10.3390/antiox10091354
|View full text |Cite
|
Sign up to set email alerts
|

Dry-Cured Ham-Derived Peptide (Asp–Leu–Glu–Glu) Exerts Cytoprotective Capacity in Human Intestinal Epithelial Caco-2 Cells

Abstract: Dry-cured hams are well-known and highly appreciated products in the Mediterranean and China. The long-term fermentation endows dry-cured hams with a unique flavor and quality. Our previous study has identified Asp–Leu–Glu–Glu (DLEE) from dry-cured Xuanwei ham with remarkable antioxidant capacity. In the current study, the Caco-2 cells were cultured in vitro and treated with different doses of DLEE. The cellular reactive oxygen species (ROS) level and antioxidant enzyme activities were then determined to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Similarly to what was highlighted in the studies reported above, Xing L. et al (2021) observed that the dry-cured ham-derived peptide DLEE protected from ROS production and that some Nrf2-ARE regulated enzymes (GR, CAT and Gpx) increased their activity after the treatment of Caco-2 cells with the peptide [ 73 ]. The authors observed that the Nrf2 and Keap1 expression changed when the cells were treated with the DLEE.…”
Section: From In Silico Analysis To Cellular Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly to what was highlighted in the studies reported above, Xing L. et al (2021) observed that the dry-cured ham-derived peptide DLEE protected from ROS production and that some Nrf2-ARE regulated enzymes (GR, CAT and Gpx) increased their activity after the treatment of Caco-2 cells with the peptide [ 73 ]. The authors observed that the Nrf2 and Keap1 expression changed when the cells were treated with the DLEE.…”
Section: From In Silico Analysis To Cellular Studiesmentioning
confidence: 72%
“…In order to confirm these results, a molecular docking analysis was performed. The DLEEs most active binding site was located in the central active pocket of the Kelch domain, involving Val418, Val465, Ile416, Arg415 and Val420 [ 73 ].…”
Section: From In Silico Analysis To Cellular Studiesmentioning
confidence: 99%
“…In contrast, the pathway by which antioxidants protect against oxidative damage by upregulating the activity and expression of endogenous antioxidant enzymes and non-enzymes is considered an indirect antioxidant capacity. Numerous studies have shown that when the balance between intracellular oxidant production and antioxidant concentration is disrupted, exogenous antioxidant peptides can act together through both pathways, exhibiting efficient inter-biomolecular synergism, hence such antioxidants are also referred to as bifunctional antioxidants [ 29 , 30 , 31 ]. The Keap1/Nrf2/ARE (full name Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-associated factor-antioxidant response element) system is a key transcription factor regulatory pathway that coordinates the expression of cellular antioxidant protective genes [ 32 ] ( Figure 2 ).…”
Section: Methods Of Activity Evaluation and Mechanisms Of Action Of A...mentioning
confidence: 99%
“…Commonly used separation and purification techniques include ultrafiltration, gel filtration chromatography, ion exchange chromatography, affinity chromatography, and reversed-phase highperformance liquid chromatography (RP-HPLC) [17,30,39,40]. The structure of the polypeptides can be further identified through high-performance liquid phase chromatography-tandem mass detector (HPLC-MS) and nuclear magnetic resonance (NMR) [26]. Figure 2 summarized the methods used for the antioxidant peptides research derived from meat protein.…”
Section: Isolation and Identification Of Antioxidant Peptidesmentioning
confidence: 99%
“…Compared with the method of producing antioxidant peptides by endogenous enzymes, the exogenous enzymatic hydrolysis method is more rapid, convenient to control, and easy to repeat [7]. Various antioxidant peptides of animal muscle protein or processing by-products such as duck meat, pork, pig blood, beef, chicken, and chicken blood have been obtained by enzymatic hydrolysis [6,18,[23][24][25][26]. In addition, during the long-term fermentation process in fermented meat products, such as ham and fermented intestines, the protein is strongly hydrolyzed under the action of various endogenous enzymes and microorganisms to generate abundant peptides and small peptides [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%